(untitled) (World Bulletin of Social Sciences, 2025)
The work of Isomiddin Ahmed Tashkuprizada, a famous encyclopedic scientist who lived and worked in the Ottoman Empire in the XVI century, “Mavduat al-ulum” is one of the rarest sources on the classification of Sciences. This work is not only a philosophical classification, but also a logical continuation and the end of the researches of Ibn An-Nadim, al-Khwarizmi, al-Farabi, Ibn Sina and Ibn Al-Akfani in the field of classification of Sciences. Over time, the fields of science have evolved, with integration and differentiation processes taking place. Some of the disciplines that were classified as separate sciences in Tashkuprizade’s “Mavduat al-ulum” have lost their significance or are now out of use. But the science of Islamic religion, which is classified in the work, has not lost its relevance even today. More details about these can be found in the article.